Rule-based fuzzy classifier for spinal deformities - (:unkn) unknown (IOS PRESS, 2014)
In this paper, 2-steps software using image processing and enhancement technologies is developed to obtain a scoliosis patient's spine pattern from 2D coronal X-Ray images without manual land marking. Then, a Rule-based Fuzzy classifier is implemented on those images to classify the spine patterns using the King-Moe classification approach.
Keywords: Image processing; scoliosis; king-moe type classification; fuzzy logic; computer aided classification; rule-based classification; RELIABILITY; SCOLIOSIS; INTRAOBSERVER; INTEROBSERVER